2020
DOI: 10.1186/s12944-020-01317-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between atherogenic index of plasma and coronary artery calcification progression in Korean adults

Abstract: Background: Dyslipidemia is a well-known risk factor for cardiovascular disease (CVD). Recently, atherogenic index of plasma (AIP) has been proposed as a novel predictive marker for CVD, and few cross sectional studies have demonstrated a relationship between AIP and coronary artery disease. The present study investigated the association between AIP and the progression of coronary artery calcification (CAC) in Korean adults without CVD. Methods: A total of 1124 participants who had undergone CAC measurement at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 28 publications
0
23
0
4
Order By: Relevance
“…Furthermore, AIP can provide information on the severity of insulin resistance [10], which is associated with impaired glucose metabolism. Recently, AIP was reported as a novel independent prognostic biomarker of coronary artery disease [11][12][13][14][15] and arterial stiffness [16] beyond traditional risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, AIP can provide information on the severity of insulin resistance [10], which is associated with impaired glucose metabolism. Recently, AIP was reported as a novel independent prognostic biomarker of coronary artery disease [11][12][13][14][15] and arterial stiffness [16] beyond traditional risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, Frohlich J et al found that the AIP was an independent predictor of angiographically defined CAD only when FER (HDL) was omitted from multivariate analysis, which may be due to a clear internal correlation between the AIP and FER (HDL) [ 20 ]. Moreover, Nam JS et al found that there is a significant correlation between the AIP and the progression of coronary artery calcification measured by using multidetector computed tomography in subjects without cardiovascular disease [ 31 ]. Furthermore, in a prospective cohort study including 2676 middle-aged adults followed for 7.8 years, researchers demonstrated that the top quartiles of the AIP predicted significantly age-adjusted incident CAD in both sexes, more strongly in women, after adjustment for C-reactive protein and traditional risk factors [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, AIP can be presumed to reflect the lipid characteristics of diabetic patients. Recently, AIP has been demonstrated to be associated with cardiovascular outcomes in the general population and different patient groups [20][21][22][23][24][25][26][27][28][29][30][31]. However, the prognostic impact of AIP on admission among T2DM patients with ACS undergoing PCI has not been exclusively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, Frohlich J, et al found that AIP was an independent predictor of angiographically de ned CAD only when FER(HDL) was omitted from multivariate analysis, which may be due to a clear internal correlation between AIP and FER(HDL) [17]. Moreover, Nam JS, et al found that there is a signi cant correlation between AIP and the progression of coronary artery calci cation measured by using a multi-detector computed tomography in subjects without cardiovascular disease [28]. Furthermore, in a prospective cohort study including 2676 middle-aged adults followed for 7.8 years, researchers demonstrated that the top quartiles of AIP predicted signi cantly age-adjusted incident CAD in both sexes, more strongly in women, after adjustment for C-reactive protein and traditional risk factors [18].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, we presume that AIP can better re ect the lipid characteristics of diabetic patients. Recently, AIP has been demonstrated to be associated with CV morbidity and mortality in general population and different patients groups [17][18][19][20][21][22][23][24][25][26][27][28]. However, the prognostic impact of AIP on admission among T2DM patients with ACS undergoing PCI has not been exclusively studied.…”
Section: Introductionmentioning
confidence: 99%